Cloud Transformation and Cybersecurity: Using AI for Securing Data Migration and Optimizing Cloud Operations in Agile Environments (Journal of Science & Technology, 2020)
The rapid adoption of cloud computing in recent years has driven enterprises to embark on cloud transformation journeys, seeking enhanced scalability, flexibility, and cost-efficiency. However, the migration of critical data to cloud environments poses significant challenges, especially in ensuring robust cybersecurity during the transformation process. The increasing complexity of cloud infrastructures and the diverse range of vulnerabilities that emerge during cloud migration have amplified the need for more advanced and automated security measures. Artificial Intelligence (AI) has emerged as a pivotal enabler in this context, offering advanced capabilities to secure data migration and optimize cloud operations. This research paper explores the application of AI-driven solutions for enhancing cybersecurity during cloud transformation, with a particular focus on securing data migration, detecting anomalies, and optimizing cloud operations in Agile environments.